TRAINING EVALUATION OF ELEMENTARY SCHOOL TEACHERS OF 3T REGIONS OF MAHAKAM ULU REGENCY BY USING KIRKPATRICK - Prijowuntato, Sebastianus Widanarto; Widharyanto, Bonifasius (Sanata Dharma University Yogyakarta, 2021)
This study aims to determine the success of training for elementary school teachers in Mahakam Ulu Regency, North Kalimantan in 2016 and 2017. The evaluation method used is the evaluation method proposed by Kirkpatrick. In this study, two of the four levels were investigated. The study method used is the Kirkpatrik evaluation model level one and two. At level one, participants conduct evaluations related to satisfaction and level two participants evaluate learning. At level one, participants are asked to fill in satisfaction instruments. The results of the satisfaction instrument entry were analyzed using weighting on each of the satisfaction dimensions. At level two, participants are asked to work on the pre-test and post-test instruments. Data were analyzed using the Wilcoxon Test. The results showed that the level of participant satisfaction for first level was 83.848% for 2015 and 83,178% for 2016. Both scores showed positive reactions to the training. For For second level, learning, the average increase in knowledge was 10.984 for 2015 and 9.4 for 2016. The increase in the mean score was significantly based on the Wilcoxon test.